EKSISTENSI PERKAWINAN EKSOGAMI MASYARAKAT SUKU GAYO DI LINGKUNGAN PERKOTAAN DAN PERDESAAN (Studi Penelitian di Kecamatan Lut Tawar dan Kecamatan Linge Kabupaten Aceh Tengah) - nofrin ariska beru sembiring; Jamaluddin J; Faisal F (JURNAL ILMIAH MAHASISWA FAKULTAS HUKUM UNIVERSITAS MALIKUSSALEH, 2021)
Abstrak The Gayo tribe community is prohibited from carrying out exogamous marriages for several reasons, one of which is that they consider one clan / split to be one offspring. The Gayo tribe community still maintains this custom and cannot be violated, if the Gayo people marry into one clan / split or one village with girls in the village then this is considered a disgrace and will have a direct impact on being ostracized by the community in that village. Communities who carry out exogamous marriages will be subject to customary sanctions in the form of farak (exile) which is decided by customary deliberations conducted by Sarak Opat (customary institution). But in reality, there are still Gayo people in urban and rural areas who carry out exogamous marriages. This study aims to determine and explain the Exogamy Marriage Exogamy of the Gayo Tribe between urban and rural areas in Central Aceh Regency, to find out and explain the legal consequences of exogamous marriages in urban and rural areas for the Gayo tribe in Central Aceh District and efforts to resolve customary sanctions given to people who carry out exogamous marriages in Central Aceh District. This study uses a qualitative method with an empirical juridical approach. Data obtained through library research (library research) and supported by field research (field research). Data analysis was carried out descriptively (descriptive analysis). Based on the results of the research, it is known that exogamous marriage in urban communities has maintained the prohibition of marrying one clan / split until now, while in rural communities the prohibition of marrying among tribes is not really cared about because there has been a shift in customs in the countryside. So that the customs in the Gayo Tribe, not all people of Central Aceh District comply with the customary prohibition of exogamous marriage. The leniency of customs in several places, especially in Linge District, is because the majority of pentani communities from outside the region who carry out exogamous marriages due to ignorance of local customary rules. It is recommended for the community to continue to maintain the customs in the Gayo Tribe. Gayo and Reje Adat Majlis so that they can provide guidance to all rural communities so that they understand and know the local customs rules because the Gayo Tribe customs are the norms (rules) for all people in Central Aceh Regency that must be obeyed. Keywords: Exogamy Marriage of the Gayo Tribe, Traditional Gayo Tribe, Sanctions of Gayo Tribe Customary Law, and Differences in the Application of Gayo Customs.